Pengaruh Beauty Influencer Dan Kualitas Produk Terhadap Keputusan Pembelian Brand Make Over Tahun 2023 - Apsari, Aisyah Putri; Maulana, Asep (Peneliti.net, 2024)
This study aims to examine and analyze the influence of Beauty Influencers and Product Quality on Purchase Decisions for make-over brands. This study uses a quantitative method with a descriptive and verification approach. The population in this study were followers of the @makeoverid Instagram account. Using the Isaac and Michael formula to determine the sample size, we found 395 respondents. The sampling method used in this research is non-probability sampling with a simple random sampling technique. This study used a range-of-scale analysis technique and multiple linear regression analysis with tools from SPSS 29 data software and Microsoft Excel 2013. The results of this study showed that there was a partial influence between Beauty Influencers (X1) and Purchase Decisions (Y) with a value of 17.8%. In comparison, the partial influence between Product Quality (X2) and Purchase Decision (Y) has a value of 49.7%. The simultaneous influence of Beauty Influencer (X1) and Product Quality (X2) on Purchase Decision (Y) obtained a value of 67.5%, and the remaining 32.5% was influenced by other variables not examined.